2017
DOI: 10.14302/issn.2575-7881.jdrr-17-1749
|View full text |Cite
|
Sign up to set email alerts
|

Template independent synthesis of nucleic acid libraries

Abstract: Though, directed evolution/In vitro evolution has greatly enhanced the applicability of natural biomolecules, there is still a big void in synthetic biology, which could be filled only when we are able to make novel/synthetic functional biomolecules. Terminal deoxyribonucleotidyl transferase (TdT) is the only known DNA polymerase, which can add deoxyribonucleotides without the requirement of a DNA template. Here, we are introducing the concept of Template-Independent Synthesis of Nucleic Acids (TISNA), where w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…They demonstrated that the ratio of nucleotide concentration to initiator concentration can affect the size distribution of the products. It is worth noting that upon introducing a mix of dNTPs, the size distributions of the resultant polynucleotides broaden significantly, observed as smears in native gels [21,22] …”
Section: Properties Of Tdt Enzymementioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that the ratio of nucleotide concentration to initiator concentration can affect the size distribution of the products. It is worth noting that upon introducing a mix of dNTPs, the size distributions of the resultant polynucleotides broaden significantly, observed as smears in native gels [21,22] …”
Section: Properties Of Tdt Enzymementioning
confidence: 99%
“…It is worth noting that upon introducing a mix of dNTPs, the size distributions of the resultant polynucleotides broaden significantly, observed as smears in native gels. [21,22]…”
Section: Properties Of Tdt Enzymementioning
confidence: 99%